The Benefits of Dark Tourism Experience among Visitors in Malaysia - Jamin, Aziean; Mohd Zain, Zainab; Rosnita Sakarji, Siti; Ahmad, Nurbarirah; Mayang Delima Mohd Beta, Raja (KnE Social Sciences, 2020)
Tourists are continuously searching for new trends, exciting ways of traveling and a variety of adrenaline rush experiences. Dark tourism is one of many examples of tourism products that able to fulfill these objectives. Although Malaysia has many dark tourism sites, they are not globally recognized yet and able to attract international tourists. Many focused on the negative impacts of the sites rather than the potential benefits of the industry. Thus, this study is prepared to investigate the benefits of dark tourism among visitors. The study adopted a model from Kang, Scott, Lee, and Ballantyne (2012). Three factors including social benefits, learning benefits, and psychological benefits were discussed. The findings have shown that dark tourism contributes sufficient benefits which may aid the rapid development of this tourism sector in the future. Keywords: Dark tourism, Paranormal, Tourism trend, Malaysia